Normal variation of clinical mobility of the mandibular symphysis in cats - Minei, Sergio; Auriemma, Edoardo; Bonacini, Serena; Kent, Michael S.; Gracis, Margherita (Frontiers in Veterinary Science, 2024)
Introduction The primary objective of this retrospective study was to document the normal variation of clinical mobility of the mandibular symphysis in cats and possible associations with bodyweight, age, sex, sexual status, breed and skull morphology. Secondarily, the radiographic appearance of the mandibular symphysis and possible associations with the analyzed data were evaluated. Materials and methods Two hundred and sixteen cats of 15 different breeds that underwent maxillofacial, oral and dental procedures from April 2015 to December 2021 were included. Clinical mobility was evaluated under general anesthesia using a 0 to 3 scale in lateromedial (LM) and dorsoventral (DV) directions. The symphysis was radiographically classified on the occlusal radiographic view of the rostral mandibles as fused or open, and with parallel or divergent margins. Results Bodyweight ranged from 2.2 to 12.5 kg (median 4.0 kg), age from 4 months to 17 years and 4 months (median 6 years and 4 months). At the first evaluation DV symphyseal mobility was 0 in 177 cases (82%), 1 in 32 cases (14.8%) and 2 in 7 cases (3.2%), LM mobility was 0 in 61 cases (28.3%), 1 in 110 cases (50.9%) and 2 in 45 cases (20.8%). 81.1% of the radiographs were included in the statistical analysis. Three symphyses (1.6%) were classified as fused and 190 (98.4%) as open, 129 (68.8%) having divergent margins and 61 (31.6%) parallel. One hundred and forty-eight cases (76.7%) did not show the presence of odontoclastic replacement resorption on the canine teeth (TR subgroup 1), 23 (11.9%) showed stage ≤3 lesions (TR subgroup 2) and 22 (11.4%) stage 4 lesions (TR subgroup 3). Logistic regression models exploring factors that affected DV and LM mobility were statistically significant (p < 0.0001; p < 0.0001) with an increase in LM mobility predicting an increase in DV mobility, and vice versa. An increase in DV mobility was associated with an increase in age and in having resorptive lesions. A decrease in LM symphyseal mobility was associated with being brachycephalic. Conclusion The great majority of cases showed some degree of LM symphyseal mobility, and 18% showed DV mobility. Symphyseal bony fusion is rare but possible.